Cerebrovascular Remodeling and Epilepsy. (June 2013) - Marchi, Nicola; Lerner-Natoli, Mireille
The role of the blood-brain barrier (BBB) in epilepsy has evolved from an obstacle for drug brain delivery to an etiological factor contributing to seizures. Recent evidence has shown cerebrovascular angiogenesis and increased BBB permeability in the epileptic foci of patients and in experimental models of seizure. The molecular players involved in cerebrovascular remodeling in the epileptic brain are similar to those reported for other brain disorders. The question arises whether pharmacological solutions restoring a proper BBB permeability and preventing dysregulated angiogenesis could be also beneficial in mitigating seizures. We now summarize the available data supporting the role of vascular remodeling and angiogenesis in the epileptic brain, taking into account that the BBB is a multi-cellular structure, reacting to physiological and pathological stimuli. Drugs targeting aberrant angiogenesis could be beneficial in reducing seizure burden when used in combination with available anti-epileptic drugs. We also offer an overview of novel cellular players, such as pericytes, which may participate in cerebrovascular remodeling in the epileptic brain. The possible role of angiogenesis in drug-resistant forms of epilepsy associated with neurovascular dysplasia is discussed. Finally, we speculate on whether the formation of leaky BBB vessels could have an impact on the cerebrovascular rheology and on the physiological mechanisms regulating brain homeostasis.